Status of global economic powers (BRICS, EU28, JAPAN, USA): The case for competitiveness and factors influencing progress or decline - Staníčková, Michaela; Fojtíková, Lenka (Univerzita Pardubice, 2018)
Many of the competitiveness challenges we see today stem from the aftermath of the financial crisis. Today, productivity and growth are not picking up in advanced economies, and the consequences of low and even negative productivity growth in many emerging economies are now evident. Productivity of major world economies can be seen as the source of national performance and subsequent international competitiveness. The paper deals with an application of Data Envelopment Analysis (DEA) method to multi-criteria performance evaluation of countries considered as global economic powers. The aim of the paper is to analyse development of and measure level of productive potential achieved by BRICS countries, the European Union (EU) and its members, Japan and the United States of America (USA) with the help of specialised DEA approach – the Output- Oriented Malmquist Productivity Index in reference period 2007-2016. Using of DEA is convenient due to set of different factors determining productivity, such as Global Competitiveness Index (GCI). Results confirm the constantly strong position of the post-war triad (in order of the EU, USA, and Japan) compared to rapidly developing BRICS countries. It is also evident the growing tendency and corresponding comparison of BRICS performance with traditional economic powers, i.e. triad.
Keywords: competitiveness; DEA; economic power; efficiency; global competitiveness index; malmquist productivity index; productivity; C61; C67; E60; F02; F62; O11; O47